Pembakuan Qira'at ‘Asim Riwayat hafs dalam Sejarah dan Jejaknya di Indonesia - Azammi, Mustofa (SUHUF, 2011)
There are at least seven types of qira’at (ways of Qur’anic recitation) used by Muslims to recite the Qur’an whose authenticity is agreed upon by Muslim scholars. However, of the seven types of Qur’anic recitation, it is that of ‘Asim that is used most widely by the Muslims all over the world, including in Indonesia. This article explains the factors which led to the widespread adoption and implementation of the Qur’anic recitation of ‘Asim, based on the narration of Hafs. Apart from the high quality of its chain of transmission and the ease of recitation, another reason for the wide dissemination of ‘Asim’s recitation is the factor of (temporal) power. The spread of this version of recitation (qira’at) can be traced through publications of the Qur’an in various countries, including in Indonesia.